Saami People and Their Everyday Culture in Film and Non-fiction from the First Half of the Twentieth Century - Chacińska, Maja (Studia Scandinavica, 2021)
The Saami people are indigenous people and ethnic minorities living in Sápmi, which encompasses the northern areas of Finland, Norway, Sweden, and the Kola Peninsula in Russia. At the beginning of the twentieth century, interest in Saami began to grow among Swedish researchers, journalists, writers, and film-makers (Jordahl 2014). The aim of this article is to compare the depiction of the attributes of Sami identity as reconstructed in cultural texts from the first half of the twentieth century. The main subject of the analysis is the Swedish feature film Midnattssolens son (The Son of the Midnight Sun) directed by Rolf Husberg and Thor L. Brooks from 1939 and the non-fiction book by the Swedish journalist Ester Blenda Nordström Kåtornas folk (People of the Cots) from 1916. The Saami people are indigenous people and ethnic minorities living in Sápmi, which encompasses the northern areas of Finland, Norway, Sweden, and the Kola Peninsula in Russia. At the beginning of the twentieth century, interest in Saami began to grow among Swedish researchers, journalists, writers, and film-makers (Jordahl 2014). The aim of this article is to compare the depiction of the attributes of Sami identity as reconstructed in cultural texts from the first half of the twentieth century. The main subject of the analysis is the Swedish feature film Midnattssolens son (The Son of the Midnight Sun) directed by Rolf Husberg and Thor L. Brooks from 1939 and the non-fiction book by the Swedish journalist Ester Blenda Nordström Kåtornas folk (People of the Cots) from 1916.